ANALISIS DISTRIBUSI PENCEMARAN BIOLOGICAL OXYGEN DEMAND (BOD) DAN DISSOLVED OXYGEN (DO) DENGAN METODE GEOGRAPHIC INFORMATION SYSTEM (GIS) DAN STREETER PHELPS DI SEPANJANGKALI SURABAYA - Muhammad Rasich Nabil Adis; Naniek Ratni Juliardi AR (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
Surabaya River is a second class (class II) river that flows from DAM Lengkong Mojokerto to DAM Jagir Surabaya. Surabaya River potentially polluted from industries around it, because 29% land around Surabaya River used for industrial area. The purpose of this study was to find out the BOD and DO distribution pattern using Geographic Information System (GIS) method and its relationship with self-purification process in Surabaya River. From the research, it found that the BOD value in Surabaya River is over the class II water quality standadts. Based on regression statistical analysis, it found that the most affect of the BOD value in Surabaya River was DO. The higher flow discharge, DO, and pH values the lower BOD value. But if the temperature value increases, the BOD value also increases too. Surabaya River has characteristics deoxygenation constant value (K1) is 0.12 – 0.20 /day and the reaeration constant value (K2) is 0.29 – 0.54 /day. This constant value (K1 and K2) greatly affect the Streeter-Phelps self-purification equation. With the distance of 0.3 Km from point 1 to point 2 DO has increased by 0.52 mg/lt. Whereas at point 9 to point 12 with the distance of 1.2 Km there is an increase in DO of 0.80 mg/lt. At longer distance, the ability of self-purification will be better if there will be no longer input into the river.